VOCATIONAL INTERNSHIP MANAGEMENT IN THE FASHION INDUSTRY: A CASE STUDY AT YECE BY YETI TOPIAH - Mutiara Nur'aini; Nurul Aini Aini; Esin Sintawati; Hapsari Kusumawardani (Jurnal Ilmiah Pendidikan Citra Bakti, 2026)
Programs for vocational internships are crucial for matching industry demands with vocational education. Nonetheless, little research has been done on internship management in the creative fashion sector, especially in fashion houses that integrate technical and artistic education. The management of vocational internship students at the Yece by Yeti Topiah fashion house in Malang, Indonesia, is the focus of this study. This study employed a qualitative descriptive methodology. Eight vocational high school students, internship supervisors, and the owner of the fashion house were interviewed, observed, and documented. The Miles and Huberman interactive model was used to analyse the data, and source triangulation was used to guarantee the validity of the data.The results demonstrate the methodical planning, execution, and assessment phases of internship management at Yece. Students took part in design, pattern-making, sewing, finishing, fashion events, and product photography, among other phases of the fashion production process. Both technical and soft skills—such as teamwork, communication, creativity, discipline, and professional responsibility—were enhanced by the program. This study contributes to vocational education research by presenting a competency-based and industry-collaborative internship management model in the fashion sector. According to the results, fashion houses can work well as collaborators to promote hands-on, industry-focused vocational education.